(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
. Stephen King’s The Dead Zone (1979) is often celebrated for its supernatural suspense, yet beneath its thrilling surface lies a profound commentary on American society. This article explores the novel’s depiction of political corruption, mental health, and the ethical dilemmas of foresight, arguing that King uses his protagonist’s psychic abilities as a lens through which to critique systemic injustices and societal fears during the Cold War era. Drawing on sociological and literary theory, the article demonstrates how King transforms genre fiction into a powerful medium for social critique.